THE EFFECTIVENESS OF USING RECIPROCAL TEACHING METHOD TO IMPROVE STUDENT READING COMPREHENSION IN NARRATIVE AT SMK NU PACE NGANJUK - Nur Rohmatus Rizki; Rina Puji Utami (Journal of English Language Education, 2026)
Reading is the process of constructing meaning from written texts, which involves not only recognizing words but also understanding, interpreting, and connecting information with prior knowledge to achieve comprehension. This study investigates the effectiveness of the Reciprocal Teaching method in improving students’ reading comprehension of narrative texts. The research was conducted at SMK NU Pace with eleventh- grade students of class XI TKJ-2 in the academic year 2024/2025. A pre-experimental design with one group pre- test and post-test was applied, involving 30 students as the sample. Data were collected through reading comprehension tests and analyzed using a paired sample t-test.The results showed that the students’ mean score improved from 47.14 in the pre-test to 76.96 in the post-test. The significance value obtained was 0.000 (p < 0.05), confirming a significant difference before and after the implementation of Reciprocal Teaching. These findings prove that Reciprocal Teaching, supported by Padlet as a collaborative medium, is effective in enhancing students’ reading comprehension, critical thinking, and learning engagement.